2018
DOI: 10.1128/iai.00423-18
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunoprotective Proteins of Streptococcus pneumoniae Identified by Opsonophagocytosis Killing Screen

Abstract: The success of polysaccharide conjugate vaccines represents a major advance in the prevention of pneumococcal disease, but the power of these vaccines is limited by partial spectrum of coverage and high cost. Vaccines using immunoprotective proteins are a promising alternative type of pneumococcal vaccines. In this study, we constructed a library of antisera against conserved pneumococcal proteins predicted to be associated with cell surface or virulence using a combination of bioinformatic prediction and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 77 publications
(103 reference statements)
1
18
0
Order By: Relevance
“…Our present results provide encouragement that the modified OPKA that detects protection by antibody to PspA (51) might also be useful as an in vitro functional assay for human antibody to PspA. It should also be noted that, using a different OPKA to study antisera to 17 separate proteins, it was found that of the 17 different OPKA-positive antisera, all but 1 gave passive protection in mice (52).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our present results provide encouragement that the modified OPKA that detects protection by antibody to PspA (51) might also be useful as an in vitro functional assay for human antibody to PspA. It should also be noted that, using a different OPKA to study antisera to 17 separate proteins, it was found that of the 17 different OPKA-positive antisera, all but 1 gave passive protection in mice (52).…”
Section: Discussionsupporting
confidence: 59%
“…It is well established that human and mouse antibodies to PspA can actively and passively protect mice from lethal pneumococcal challenge (9, 15, 52, 55, 56). One hurdle that must be overcome for PspA to move into efficacy trials has been the lack of an accepted in vitro functional assay to screen sera from immunized humans for changes in their protective potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A key attribute commonly associated with efficacy of CPS specific Ab-mediated immunity is opsonophagocytosis (22, 23). To assess the efficacy of different PD poly-IgGs, we performed opsonophagocytosis experiments in J774 macrophages with Poly-IgG #207 , poly-IgG #219 , and poly-IgG #116 purified from patients infected with SBU219 ( wzi154 ), SBU116 ( wzi50 ), and SBU207 ( wz i 29 ).…”
Section: Resultsmentioning
confidence: 99%